Okara Probiotic Drink as An Innovative Product from Tofu By-Product: Community Counselling for Young Tofu Craftsmen - Simamora, Adelina; Santoso, Adit Widodo; Marvianta , Yohannes Bosco Andre; Purba, Florensa Rosani; Timotius, Kris Herawan (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tofu production produces a large amount of by-product, known as okara. It is estimated that 60% of the soybeans used in tofu processing turns into okara. Thus far, okara is used for cattle feed. Utilization of okara for probiotic drink can potentially increase economic value of okara. The community service activity (PKM) was undertaken in Semanan tofu production centre, which is one of the largest tofu production sites in Jakarta. The service activity aimed to increase knowledge among tofu craftsmen towards the utilization of okara for probiotic drink. The PKM activity was carried out by means of online counselling and training activities. Twenty-seven tofu craftsmen took part in the sharing program. Four stages of activities were conducted to implement the sharing program, comprised of needs and field assessments, recruitment of participants, preparation of online materials, and online counselling. Pre- and post-tests were conducted to evaluate participants’ knowledge. The mean pre- and post-tests were 51.4 ± 22.3 and 76.9 ± 25.8, indicating a significant improve in the knowledge about okara, probiotic drink, and okara-based probiotic drinks due to community service activity. The counselling activity succeeded to raise the knowledge about okara probiotic drink among participants.